Effect of Collector Reagent Variations in the Flotation Process on the Percentage of Mass Recovery & Metal Recovery - Fitri Ayu Mardhatila; Azalia Songli; Nurul Wulandari; Azaria Songli; Untung Sukamto (Proceeding of the International Conferences on Engineering Sciences, 2024)
Indonesia is a country with abundant gold minerals and it is quite economical to mine. Processing gold minerals is very important to increase gold content, one of the methods used is flotation. Reagent knowledge test in gold ore flotation was carried out to obtain certain mass recovery and metal recovery. In this study, the reagents used were 621 (activator), 530X (frother), and several collectors, namely collector type 1, namely 4000, collector type 3, namely X2, and the reagent test used a varied collector on collector 2, namely with reagent 7042; 7042A; 7042W and without using collector 2. Optimal % mass recovery and % metal recovery results using a variation of collector 2 reagent in the form of 7042 which produces a high recovery value of 4.19% in the final concentrate and a high metal recovery of 85.73%